Taming the bias zoo - Liu, Hongqi; Peng, Cameron; Xiong, Wei A.; Xiong, Wei (Journal of Financial Economics, 2022)
The success of behavioral economics has led to a new challenge: many biases offer observationally similar predictions for a targeted financial anomaly. To tame this bias zoo, we combine subjective survey responses with observational data to propose a new approach, one that is robust to question-specific biases introduced through surveys. We illustrate this approach by administering a nationwide survey of Chinese retail investors to elicit their trading motives. In cross-sectional regressions of respondents’ actual turnover on survey-based trading motives, perceived information advantage and gambling preference dominate other motives, though they are not the most prevalent biases based on survey responses.